Battery positive electrode material, preparation method thereof and positive electrode sheet

CN122950435APending Publication Date: 2026-10-20REPT BATTERO ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611122402.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明提供了一种电池正极材料及其制备方法,以解决聚合物包覆氧化物颗粒电导率差、倍率性能不足的问题

Benefits of technology

1.本发明提供一种电池正极材料的制备方法,通过将带正电碳纳米管和带银锚定点的正极氧化物材料组装得到带正电碳纳米管垂直组装在正极氧化物材料表面的复合材料,通过控制带正电碳纳米管与带银锚定点的正极氧化物材料的质量比使复合材料中碳纳米管一端与银金属颗粒位点吸附,另一端与其他同样带正电的碳纳米管形成相互排斥作用,从而保证复合材料形成带正电的碳纳米管垂直在正极氧化物材料表面的结构;垂直于正极氧化物材料表面的碳纳米管可以发挥良好的导电通道作用,进而赋予本发明所述复合材料在用作电池正极材料时的高导电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention relates to the field of battery technology, and discloses a battery cathode material, its preparation method, and a cathode electrode sheet. In this invention, positively charged carbon nanotubes (CNTs) and a cathode oxide material with silver anchoring points are assembled to obtain a composite material in which CNTs are vertically assembled on the surface of the cathode oxide material. In the composite material, one end of the CNTs adsorbs onto silver metal particle sites, while the other end forms a repulsive interaction with other positively charged CNTs. This ensures that the composite material forms a structure where positively charged CNTs are vertically assembled on the surface of the cathode oxide material. The vertically assembled CNTs can function as good conductive channels, ensuring that the battery cathode material prepared by this invention has high conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a battery positive electrode material, its preparation method, and a positive electrode sheet. Background Technology

[0002] Currently, the main cathode materials for sodium-ion batteries include oxides, polyanions, and Prussian blue materials. Among them, layered oxides have great potential for application in commercial vehicles and passenger vehicles due to their advantages such as high specific capacity, high rate capability, and high voltage platform.

[0003] Due to their high electrochemical activity, oxide-based cathode materials are relatively unstable under high-temperature operating conditions, exhibiting numerous side reactions and severe gas generation, leading to a precipitous drop in battery cycle capacity and posing safety hazards. In existing technologies, polymer coating of oxide particles is an effective means of suppressing side reactions and reducing gas generation; however, polymer coating of oxide particles alone suffers from poor conductivity and rate performance. Current technologies address the poor conductivity issue by adding conductive particles to the polymer layer; however, the addition of conductive particles generally fails to fully utilize their conductive properties, resulting in unsatisfactory conductivity improvement.

[0004] Therefore, there is an urgent need to provide a cathode material that balances high-temperature cycling stability, conductivity, and rate performance. Summary of the Invention

[0005] This invention provides a battery cathode material and its preparation method to solve the problems of poor conductivity and insufficient rate performance of polymer-coated oxide particles.

[0006] In a first aspect, the present invention provides a method for preparing a battery cathode material, comprising the following steps: A composite material is obtained by assembling positively charged carbon nanotubes and positively charged oxide materials with silver anchors, wherein the mass ratio of the positively charged oxide material with silver anchors to the positively charged carbon nanotubes is 1:(0.05-0.3).

[0007] In one optional embodiment, the mass ratio of the silver-anchored positive oxide material to the positively charged carbon nanotube is 1:(0.08-0.29), which can be 1:0.08, 1:0.13, 1:0.17, 1:0.20, or 1:0.29.

[0008] In one optional embodiment, the preparation method of the composite material includes: reacting the silver-anchored positive oxide material with the dispersion of positively charged carbon nanotubes when the pH of the system is 5-7; the pH of the system is preferably 5.5-6.5; the reaction includes stirring and separation steps; the separation step includes washing the precipitate with water after centrifugation, and then vacuum drying the washed precipitate at a certain temperature; And / or, the method for preparing the positively charged carbon nanotubes includes: mixing carbon nanotubes, cationic polymers, dispersants and water to form a dispersion, adjusting the pH of the dispersion to 7.0-8.0, and stirring; the stirring process further includes a separation step, wherein the separation step includes centrifugation followed by washing the precipitate with water; And / or, the preparation method of the positive oxide material with silver anchor points includes: dispersing the positive oxide material in water, adjusting the pH of the system to 5.0-6.0, adding a silver ion source, and stirring; the stirring process further includes a separation step, which includes centrifuging, washing the precipitate with water, and then vacuum drying the washed precipitate at a certain temperature.

[0009] In one optional embodiment, the mass ratio of the cationic polymer to the carbon nanotube is (1-3):1, optionally 1:1, 2:1, or 3:1; And / or, the mass ratio of the silver ion source to the positive electrode oxide material is (0.004-0.013):1.

[0010] In one optional embodiment, the method for preparing the battery cathode material further includes the following steps: coating the composite material with an intrinsically conductive polymer to obtain a composite material with a polymer coating layer; wherein the mass ratio of the intrinsically conductive polymer to the composite material is (0.04-0.05):1, optionally 0.04:1, 0.045:1, or 0.05:1.

[0011] In one optional embodiment, the mass ratio of the cationic polymer to the carbon nanotube is (2-3):1, optionally 2:1 or 3:1; And / or, the mass ratio of the silver ion source to the positive electrode oxide material is (0.0043-0.0128):1, optionally 0.0043:1, 0.0085:1, or 0.0128:1; And / or, the mass ratio of the dispersant to the carbon nanotubes is (5-10):100, optionally 10:100.

[0012] In one optional embodiment, the cationic polymer is selected from at least one of polydiallyldimethylammonium chloride, polytrimethylallylammonium chloride, polyethyleneimine, polylysine, and polymethacryloyloxyethyltrimethylammonium chloride solvent, and optionally diallyldimethylammonium chloride. And / or, the positive electrode oxide material is a sodium ion layered oxide, optionally NaNi. 1 / 3 Co 1 / 3 Mn 1 / 3O2, NaNi 0.4 Mn 0.4 Fe 0.2 O2, NaCu 0.2 Fe 0.3 Mn 0.5 O2, Na 0.67 Fe 0.5 Mn 0.5 O2, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 At least one of O2, preferably NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2; And / or, the silver ion source is selected from at least one of silver nitrate, silver acetate, and silver oxide, and optionally silver nitrate; And / or, the dispersant is selected from at least one of sodium α-olefin sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and sodium fatty alcohol ether sulfonate, and optionally sodium α-olefin sulfonate; And / or, the carbon nanotubes are selected from at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. Optionally, the outer diameter of the carbon nanotubes is 10-20 nm, the average length of a single nanotube is 3-8 μm, and the aspect ratio is 800-1500. Further optionally, the outer diameter of the carbon nanotubes is 12-16 nm, and the average length of a single nanotube is 4-6 μm.

[0013] In one optional embodiment, the method for preparing the intrinsically conductive polymer coating the composite material includes: dissolving the intrinsically conductive polymer in an organic solvent to prepare a coating solution, dispersing the composite material in the coating solution, and stirring; the stirring process further includes a separation step, wherein the separation step includes centrifuging the precipitate, washing it with alcohol, and then vacuum drying the alcohol-washed precipitate at a certain temperature; Optionally, the mass-to-volume ratio of the intrinsically conductive polymer to the organic solvent is (0.1-1):40 g / mL, or optionally 0.2:40 g / mL; Optionally, the intrinsically conductive polymer is selected from at least one of polycarbazole, polyaniline, polypyrrole, polyindole, and polytriphenylamine, and is optionally polycarbazole; Optionally, the organic solvent is selected from at least one of N-methylpyrrolidone, dimethyl sulfoxide, N-butylpyrrolidone, and N,N-dimethylformamide, and is optionally N-methylpyrrolidone.

[0014] In a second aspect, the present invention also provides a battery cathode material, comprising the cathode oxide material, the positively charged carbon nanotubes vertically assembled on the surface of the cathode oxide material, and a polymer coating layer as described above covering the surface of the cathode oxide material; wherein, one end of the positively charged carbon nanotube is vertically connected to the surface of the cathode oxide material, and the other end is exposed on the surface of the polymer coating layer. And / or, the thickness of the polymer layer is 5-10 nm, optionally 6 nm.

[0015] Thirdly, the present invention also provides a positive electrode sheet, the positive electrode sheet comprising the battery positive electrode material, conductive agent and binder described above; Optionally, the conductive agent is selected from at least one of conductive carbon black and acetylene black, preferably conductive carbon black; Optionally, the adhesive is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polytetrafluoroethylene, preferably polyvinylidene fluoride; Optionally, the mass ratio of the sodium-ion battery cathode material, conductive agent, and binder is 8:1:1 or 7:2:1, preferably 8:1:1.

[0016] Fourthly, the present invention also provides a sodium-ion battery, the sodium-ion battery comprising the above-mentioned positive electrode, electrolyte, separator and negative electrode; The electrolyte is NaPF6, the separator is Celgard 2500, and the negative electrode is a sodium plate.

[0017] Specifically, the preparation method of the battery cathode material of the present invention is as follows: (1) Take a certain amount of carbon nanotubes (CNTs), add deionized water at a ratio of 1g:50mL, add a certain amount of dispersant, and ultrasonically disperse for 30-60min to obtain a uniform CNT dispersion; add a certain amount of cationic polymer solution to the CNT dispersion, adjust the pH of the system to 7.0-8.0 with 0.1mol / L NaOH solution, place it in a constant temperature water bath at 40-50℃, and magnetically stir at 1000-2000r / min for 30-60min to allow the cationic polymer to uniformly coat the CNT surface and introduce positively charged groups; centrifuge the dispersion after reaction at a rate of 5000-9000r / min for 5-30min, and wash the precipitate obtained after centrifugation with deionized water; redisperse the precipitate after washing in deionized water and ultrasonically for 5-30min to obtain a dispersion of positively charged CNTs.

[0018] (2) Take a certain amount of positive oxide material (N), add deionized water at a ratio of 1g:40mL, and ultrasonically disperse for 5-15min; adjust the pH of the dispersion to 5.0-6.0 with 0.1mol / L HCl solution; slowly add a certain amount of silver ion source solution to the dispersion, and magnetically stir at 1000-2000r / min for 5-30min; centrifuge at 3000-8000r / min for 5-10min, wash the precipitate obtained after centrifugation with deionized water 3 times, and vacuum dry the precipitate at 50-80℃ for 3-4h to obtain positive oxide material with silver anchor points on the surface. The prepared positive oxide material with silver anchor points was added to the dispersion of positively charged CNTs in step (1), and the pH of the system was adjusted to 5.5-6.5 with 0.1 mol / L HCl solution. The mixture was placed in a constant temperature water bath at 20-50℃ and magnetically stirred at 100-500 r / min for 60-90 min. Then it was centrifuged at 6000-9000 r / min for 10-20 min. The precipitate obtained after centrifugation was washed with deionized water, and the precipitate after washing was vacuum dried at 60-100℃ for 4-8 h to obtain the composite material N@CNT with positively charged CNTs vertically assembled on the surface of the positive oxide material. (3) Take a certain amount of intrinsically conductive polymer and NMP, place them in a constant temperature water bath at 40-60℃, and stir magnetically at 1000-2000r / min for 40-80min until the intrinsically conductive polymer is completely dissolved to obtain a uniform intrinsically conductive polymer coating solution; add the N@CNT prepared in step (2) to the intrinsically conductive polymer coating solution, disperse ultrasonically for 10-30min, stir at 50-200r / min for 20-40min; centrifuge at 5000-8000r / min for 5-10min, and wash the precipitate obtained after centrifugation with anhydrous ethanol 3 times; dry the precipitate after ethanol washing in vacuum at 60-100℃ for 4h to obtain the battery cathode material N@CNT@ICP with composite coating layer; (4) Prepare a positive electrode slurry by mixing the N@CNT@ICP, conductive agent and binder in a ratio of 8:1:1 or 7:2:1 with NMP as solvent, use carbon-coated aluminum foil as foil material, make a positive electrode sheet, and cut it into 12mm diameter round sheets for later use.

[0019] The technical solution of this invention has the following advantages: 1. This invention provides a method for preparing a battery cathode material. The method involves assembling positively charged carbon nanotubes and a cathode oxide material with silver anchoring points to obtain a composite material in which positively charged carbon nanotubes are vertically assembled on the surface of the cathode oxide material. By controlling the mass ratio of positively charged carbon nanotubes to the cathode oxide material with silver anchoring points, one end of the carbon nanotubes in the composite material is adsorbed onto silver metal particle sites, while the other end forms a repulsive interaction with other positively charged carbon nanotubes. This ensures that the composite material forms a structure in which positively charged carbon nanotubes are vertically arranged on the surface of the cathode oxide material. The carbon nanotubes perpendicular to the surface of the cathode oxide material can act as good conductive channels, thereby endowing the composite material of this invention with high conductivity when used as a battery cathode material.

[0020] 2. This invention provides a method for preparing a battery cathode material, which involves surface functionalizing carbon nanotubes with a cationic polymer to make their surface positively charged; and enriching the surface of the cathode oxide material with Ni by adjusting the pH. 2+ Fe 3+ Mn 3+ By adding silver ion sources to the dispersion of the positively charged cathode oxide material, silver metal particle sites are constructed on the surface of the cathode oxide material. This ensures that one end of the carbon nanotube is adsorbed onto the silver metal particle sites, while the other end forms mutual repulsion with other positively charged carbon nanotubes and positively charged cathode oxide materials, thereby allowing the carbon nanotubes to be vertically assembled on the surface of the cathode oxide material.

[0021] 3. This invention provides a method for preparing a battery cathode material, which involves polymer coating a composite material in which carbon nanotubes are vertically assembled on the surface of a cathode oxide material to coat the surface with an intrinsically conductive polymer layer, thereby achieving high-temperature protection for the cathode oxide material.

[0022] 4. This invention provides a method for preparing a battery cathode material. By directionally controlling the orientation of carbon nanotubes, the carbon nanotubes are made more perpendicular to the surface of the cathode oxide material, thus constructing a highly efficient electrical conductivity channel in the intrinsically conductive polymer layer, significantly improving the electrical conductivity of the cathode oxide material. By coating the intrinsically conductive polymer layer, the occurrence of side reactions between the cathode oxide material and the electrolyte is reduced, achieving isolation and protection between the oxide cathode material particles and the electrolyte, and effectively improving the cycle stability of the oxide cathode material at high temperatures.

[0023] 5. This invention provides a method for preparing a battery cathode material. This method is simple, has a low reaction temperature, and can protect the structure of the cathode oxide material itself from being damaged.

[0024] 6. This invention provides a battery cathode material, comprising a cathode oxide material, positively charged carbon nanotubes vertically assembled on the surface of the cathode oxide material, and a polymer coating layer covering the surface of the cathode oxide material; wherein one end of the positively charged carbon nanotube is vertically connected to the surface of the cathode oxide material, and the other end is exposed on the surface of the polymer coating layer. The cathode oxide material itself has good conductivity, but its high-temperature stability is poor. Coating with an intrinsically conductive polymer layer can improve the material's stability, but this coating reduces the conductivity of the cathode oxide material. This invention uses carbon nanotubes, one end vertically connected to the surface of the cathode oxide material and the other end exposed on the surface of the polymer coating layer, as conductive pathways, thus preserving good conductive channels while improving stability through the intrinsically conductive polymer coating, thereby balancing high conductivity and high-temperature stability. Detailed Implementation

[0025] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.

[0026] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0027] Example 1 This embodiment provides a battery positive electrode material, a positive electrode sheet, and a method for preparing the same, including the following steps: (1) Take 0.1 g of multi-walled carbon nanotubes (MWCNTs: outer diameter 12-16 nm, average length of a single tube 4-6 μm, aspect ratio 800-1500), add deionized water at a ratio of 1 g: 50 mL, add 0.01 g of sodium α-olefin sulfonate, and ultrasonically disperse for 40 min to obtain a uniform MWCNT dispersion; add 10 mL of polydiallyldimethylammonium chloride (PDDA) solution with a mass concentration of 0.02 g / mL to the MWCNT dispersion, adjust the pH of the above system to 7.5 with 0.1 mol / L NaOH solution, and then place it in a 45℃ constant temperature water bath and magnetically stir at 1500 r / min for 45 min to allow polydiallyldimethylammonium chloride (PDDA) to uniformly coat the surface of MWCNTs and introduce positively charged groups; centrifuge the dispersion after reaction at a rate of 7000 r / min for 15 min. (2) The precipitate obtained after centrifugation was washed three times with deionized water to obtain 0.17 g of precipitate. The precipitate (0.17 g) after washing was redispersed in 50 mL of deionized water and sonicated for 10 min to obtain a dispersion of positively charged MWCNT.

[0028] (2) Take 1g of sodium nickel iron manganate (NaNi) 1 / 3 Fe 1 / 3 Mn 1 / 3 O2) was added to deionized water at a ratio of 1g:40mL and ultrasonically dispersed for 10min; the pH of the dispersion was adjusted to 5.5 with 0.1mol / L HCl solution; 5mL of AgNO3 solution with a concentration of 0.01mol / L was slowly added dropwise to the above dispersion and magnetically stirred at 1500r / min for 20min; the mixture was centrifuged at 6000r / min for 10min, and the precipitate obtained after centrifugation was washed 3 times with deionized water. The washed precipitate was vacuum dried at 60℃ for 4h to obtain 1.0g of positive oxide material with silver anchor points on the surface; The prepared positive oxide material with silver anchor points was added to the dispersion of positively charged MWCNTs in step (1), and the pH of the system was adjusted to 6.0 with 0.1 mol / L HCl solution. Then it was placed in a constant temperature water bath at 40°C and magnetically stirred at 300 r / min for 80 min. Then it was centrifuged at 7000 r / min for 15 min. The precipitate obtained after centrifugation was washed three times with deionized water. The precipitate after washing was vacuum dried at 80°C for 6 h to obtain 1.1 g of composite material N@MWCNT with positively charged MWCNTs vertically assembled on the surface of the positive oxide material. (3) Take 0.05g of polycarbazole (PCZ) and 10mL of N-methylpyrrolidone (NMP), place them in a constant temperature water bath at 60℃, and stir magnetically at 1500r / min for 50min until the polycarbazole (PCZ) is completely dissolved to obtain a uniform polycarbazole (PCZ) coating solution; add the N@MWCNT prepared in step (2) to the polycarbazole (PCZ) coating solution, disperse ultrasonically for 10min, stir at 150r / min for 30min; then centrifuge at 6000r / min for 10min, and wash the precipitate after centrifugation with anhydrous ethanol 3 times; dry the precipitate after ethanol washing under vacuum at 95℃ for 4h to obtain a composite material with a polymer coating layer (N@MWCNT@PCZ), which is the positive electrode material of the battery; the thickness of the polymer coating layer was measured to be 6nm using a high resolution transmission electron microscope (HRTEM, JEOL JEM-2100F) at a magnification of 80000-200000 times.

[0029] (4) Prepare a positive electrode slurry by mixing N@MWCNT@PCZ, conductive carbon black, and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 and using N-methylpyrrolidone (NMP) as a solvent. Use carbon-coated aluminum foil as the foil material to make a positive electrode sheet, and cut it into 12mm diameter round sheets for later use.

[0030] The preparation method of the above positive electrode sheet is as follows: ① Take 0.0625g of PVDF and add it to 0.25mL of NMP. Stir magnetically at 1000r / min for 30min to obtain a gel solution; ② Grind and mix 0.5g of N@MWCNT@PCZ with 0.0625g of conductive carbon black for 30min. Add the mixed powder to the slurry obtained in ① and stir magnetically at 1000r / min for 6h to obtain the positive electrode slurry. Adjust the viscosity of the slurry to 8000mPa.s by adding NMP. ③ Use a 150μm gap scraper to coat the positive electrode slurry onto the carbon-coated aluminum foil (the substrate thickness is 12μm and the carbon coating layer thickness is 1μm), and dry it in an 80℃ oven for 8 hours to obtain the positive electrode sheet.

[0031] Examples 2-7 Examples 2-7 are prepared in a similar manner to Example 1, except that the mass ratio of cationic polymer to MWCNT, the mass ratio of positive oxide material to silver ion source, and the mass ratio of positive oxide material with silver anchoring point to positively charged MWCNT are different. Specifically, the amounts of MWCNT, cationic polymer, positive oxide material, and silver ion source added are different.

[0032] The specific formulations for Examples 1-7 are shown in Table 1, and the specific mass ratios between the components are shown in Table 2.

[0033] Comparative Example 1 The difference between this comparative example and Example 1 is that polydiallyldimethylammonium chloride was not added to the MWCNT dispersion in step (1). That is, the MWCNTs in the MWCNT dispersion prepared in step (1) were not surface functionalized and were not positively charged. The remaining steps are the same as in Example 1.

[0034] Comparative Example 2 The difference between this comparative example and Example 1 is that MWCNT was not added in step (1), while the rest of the steps are the same as in Example 1.

[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that no silver ion source was added in step (2), that is, there are no silver metal anchoring points on the surface of the positive oxide material in step (2). The remaining steps are the same as in Example 1.

[0036] Comparative Example 4 The difference between this comparative example and Example 1 is that in step (2), an equal amount of zinc nitrate is used instead of silver nitrate, while the remaining steps are the same as in Example 1.

[0037] The formulations for Comparative Examples 1-4 are shown in Table 1, and the mass ratios of each component are shown in Table 2.

[0038] Table 1

[0039] Table 2

[0040] Test case Sodium-ion batteries were prepared using the positive electrode sheets obtained from the various examples and comparative examples for electrochemical testing. The preparation methods are as follows: Assemble a 2032-size coin cell in the following order: negative electrode shell, spring plate, gasket, sodium plate, electrolyte addition, separator, electrolyte addition again, positive electrode plate, and positive electrode shell. The negative electrode is a 16mm diameter sodium plate, the electrolyte composition is NaPF6, and the separator is Celgard 2500.

[0041] Testing instruments: Using a battery testing system (model CT3002A, manufactured by Wuhan Landian Electronics Co., Ltd.) and a high and low temperature test chamber (model TOD-B80EWL, manufactured by Jiangsu Tuomiluo High-end Equipment Co., Ltd.), conventional testing methods were employed to test the 6C capacity retention rate (with 1C as the baseline) and the capacity retention rate after 100 cycles at 1C / 1C@50℃.

[0042] Table 3

[0043] The data in Table 3 show that the battery prepared in Example 1 has a 6C capacity retention rate (based on 1C) of 93.09%, and a capacity retention rate of 98.68% after 100 cycles at 1C / 1C@50℃. The battery has excellent high-rate fast charging / discharging performance and high-temperature cycling stability.

[0044] Compared with Example 1, the high-rate fast charging / discharging performance and high-temperature cycling stability of the battery prepared in Example 2 decreased, indicating that when the mass ratio of cationic polymer to MWCNT is 1:1, due to the reduced amount of cationic polymer added, the surface of MWCNT is not positively charged enough, resulting in MWCNT not being completely perpendicular to the surface of the positive electrode oxide material, thus limiting the conductive path.

[0045] Compared with Example 1, the high-rate fast charging / discharging performance and high-temperature cycling stability of the battery prepared in Example 3 are basically consistent with those of Example 1. This indicates that when the mass ratio of cationic polymer to MWCNT is increased from 2:1 to 3:1, that is, the amount of cationic polymer added increases, the high-rate fast charging / discharging performance and high-temperature cycling stability of the battery are not further improved.

[0046] Compared with Example 1, the high-rate fast charging / discharging performance and high-temperature cycling stability of the battery prepared in Example 4 decreased significantly. This indicates that when the amount of MWCNT added is low, there are fewer conductive pathways formed by carbon nanotubes vertically assembled on the surface of the positive electrode oxide material, resulting in a significant decrease in the high-rate fast charging / discharging performance of the battery.

[0047] Compared to Example 1, the battery prepared in Example 5 exhibits superior high-rate fast charging / discharging performance and high-temperature resistance. The slight decrease in cycle stability indicates that when the amount of MWCNT added increases, the excess MWCNT will affect the vertical distribution of other MWCNTs that have been anchored on the surface of the cathode oxide material, thereby affecting the high-rate fast charging / discharging performance and high-temperature cycle stability of the battery.

[0048] Compared with Example 1, the battery prepared in Example 6 showed a significant decrease in high-rate fast charging / discharging performance and high-temperature cycling stability. This indicates that when the amount of silver ion source added is too small, fewer anchoring points are formed on the surface of the positive oxide material, resulting in insufficient MWCNTs anchored on the surface of the positive oxide material. Furthermore, the MWCNTs are not completely perpendicular to the surface of the positive oxide material, thus limiting the conductive path and reducing battery performance.

[0049] Compared with Example 1, the high-rate fast charging / discharging performance and high-temperature cycling stability of the battery prepared in Example 7 decreased slightly. This indicates that when the amount of silver ion source added increases, too many anchoring points are formed on the surface of the positive electrode oxide material, resulting in additional sidewall adsorption in addition to adsorption at the top of MWCNTs, which interferes with the vertical alignment of MWCNTs and affects battery performance.

[0050] Compared with Example 1, the battery prepared in Comparative Example 1 showed a significant decrease in 6C capacity retention (based on 1C) and capacity retention after 1C / 1C@50℃ cycling for 100 cycles. This indicates that without surface functionalization of MWCNTs, the MWCNTs cannot be perpendicular to the surface of the positive electrode oxide material, thus limiting the conductive path and resulting in a significant decrease in the battery's high-rate fast charging / discharging performance and high-temperature cycling stability.

[0051] Compared with Example 1, the battery prepared in Comparative Example 2 showed a significant decrease in 6C capacity retention (based on 1C) and capacity retention after 1C / 1C@50℃ cycling for 100 cycles. This indicates that without MWCNT, the conductive pathway of the cathode oxide material is severely insufficient, resulting in a significant decrease in the battery's rate performance.

[0052] Compared with Example 1, the battery prepared in Comparative Example 3 showed a significant decrease in 6C capacity retention (based on 1C) and capacity retention after 1C / 1C@50℃ cycling for 100 cycles. This indicates that without constructing silver metal anchor points on the surface of the cathode oxide material, MWCNTs cannot be perpendicular to the surface of the cathode oxide material, resulting in a severe lack of conductive pathways in the cathode oxide material and a significant decrease in battery rate performance.

[0053] Compared with Example 1, the 6C capacity retention rate (based on 1C) of the battery prepared in Comparative Example 4 was significantly reduced, indicating that zinc metal could not build a stable metal anchor point on the surface of the cathode oxide material. The MWCNTs perpendicular to the surface of the cathode oxide material were very easy to fall off, resulting in a serious lack of conductive pathways in the cathode oxide material and a serious decrease in battery rate performance.

[0054] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a battery cathode material, characterized in that, Includes the following steps: Positively charged carbon nanotubes and positively charged oxide materials with silver anchors are assembled to obtain a composite material in which positively charged carbon nanotubes are vertically assembled on the surface of the positively charged oxide material; wherein, the mass ratio of the positively charged oxide with silver anchors to the positively charged carbon nanotubes is 1:(0.05-0.3).

2. The method for preparing the battery cathode material according to claim 1, characterized in that, The mass ratio of the silver-anchored positive oxide to the positively charged carbon nanotube is 1:(0.08-0.29).

3. The method for preparing the battery cathode material according to claim 1 or 2, characterized in that, The preparation method of the composite material includes: reacting the silver-anchored positive oxide material with the dispersion of positively charged carbon nanotubes when the pH of the system is 5-7; And / or, the method for preparing the positively charged carbon nanotubes includes: mixing carbon nanotubes, cationic polymers, dispersants and water to prepare a dispersion, adjusting the pH of the dispersion to 7.0-8.0, and stirring; And / or, the preparation method of the positive oxide material with silver anchor points includes: dispersing the positive oxide material in water, adjusting the pH of the system to 5.0-6.0, adding a silver ion source, and stirring.

4. The method for preparing the battery cathode material according to claim 3, characterized in that, The mass ratio of the cationic polymer to the carbon nanotubes is (1-3):1; And / or, the mass ratio of the silver ion source to the positive electrode oxide material is (0.004-0.013):

1.

5. The method for preparing the battery cathode material according to any one of claims 1-4, characterized in that, The method also includes the following steps: coating the composite material with an intrinsically conductive polymer to obtain a composite material with a polymer coating layer; the mass ratio of the intrinsically conductive polymer to the composite material is (0.04-0.05):

1.

6. The method for preparing the battery cathode material according to claim 4, characterized in that, The mass ratio of the cationic polymer to the carbon nanotubes is (2-3):1; And / or, the mass ratio of the silver ion source to the positive electrode oxide material is (0.0043-0.0128):1; And / or, the mass ratio of the dispersant to the carbon nanotubes is (5-10):

100.

7. The method for preparing the battery cathode material according to any one of claims 1-6, characterized in that, The cationic polymer is selected from at least one of polydiallyldimethylammonium chloride, polytrimethylallylammonium chloride, polyethyleneimine, polylysine, and polymethacryloyloxyethyltrimethylammonium chloride solvent, and optionally polydiallyldimethylammonium chloride. And / or, the positive electrode oxide material is a sodium ion layered oxide, optionally NaNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaNi 0.4 Mn 0.4 Fe 0.2 O2, NaCu 0.2 Fe 0.3 Mn 0.5 O2, Na 0.67 Fe 0.5 Mn 0.5 O2, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 At least one of O2; And / or, the silver ion source is selected from at least one of silver nitrate, silver acetate, and silver oxide; And / or, the dispersant is selected from at least one of sodium α-olefin sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and sodium fatty alcohol ether sulfonate; And / or, the carbon nanotubes are selected from at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

8. The method for preparing the battery cathode material according to claim 5, characterized in that, The preparation method of coating the composite material with the intrinsically conductive polymer includes: dissolving the intrinsically conductive polymer in an organic solvent to prepare a coating solution, dispersing the composite material in the coating solution, and stirring. Optionally, the mass-to-volume ratio of the intrinsically conductive polymer to the organic solvent is (0.1-1):40 g / mL; Optionally, the intrinsically conductive polymer is selected from at least one of polycarbazole, polyaniline, polypyrrole, polyindole, and polytriphenylamine; Optionally, the organic solvent is selected from at least one of N-methylpyrrolidone, dimethyl sulfoxide, N-butylpyrrolidone, and N,N-dimethylformamide, preferably N-methylpyrrolidone.

9. A battery cathode material prepared by the method according to any one of claims 1-8, characterized in that, The material includes the positive electrode oxide material, the positively charged carbon nanotubes vertically assembled on the surface of the positive electrode oxide material, and the polymer coating layer as described in claim 5 or 8 covering the surface of the positive electrode oxide material; wherein, one end of the positively charged carbon nanotube is vertically connected to the surface of the positive electrode oxide material, and the other end is exposed on the surface of the polymer coating layer. Optionally, the thickness of the polymer coating layer is 5-10 nm.

10. A positive electrode plate, characterized in that, The positive electrode sheet comprises the battery positive electrode material, conductive agent, and binder as described in claim 9; Optionally, the conductive agent is selected from at least one of conductive carbon black and acetylene black; Optionally, the adhesive is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polytetrafluoroethylene.